Comprehensive profiling of lysine ubiquitome reveals diverse functions of lysine ubiquitination in common wheat. Issue 1 (December 2017) - Zhang, Ning; Zhang, Lingran; Shi, Chaonan; Tian, Qiuzhen; Lv, Guoguo; Wang, Ying; Cui, Dangqun; Chen, Feng
Abstract Protein ubiquitination, which is a major post-translational modifications that occurs in eukaryotic cells, is involved in diverse biological processes. To date, large-scale profiling of the ubiquitome in common wheat has not been reported, despite its status as the major cereal crop in the world. Here, we performed the first ubiquitome analysis of the common wheat (Triticum aestivum L.) variety, Aikang 58. Overall, 433 lysine modification sites were identified in 285 proteins in wheat seedlings, and four putative ubiquitination motifs were revealed. In particular, 83 of the 285 ubiquitinated proteins had ubiquitination orthologs inOryza sativa L., andArabidopsis thaliana . Ubiquitylated lysines were found to have a significantly different preference for secondary structures when compared with the all lysines. In accordance with previous studies, proteins related to binding and catalytic activity were predicted to be the preferential targets of lysine ubiquitination. Besides, protein interaction network analysis reveals that diverse interactions are modulated by protein ubiquitination. Bioinformatics analysis revealed that the ubiquitinated proteins were involved in diverse biological processes. Our data provides a global view of the ubiquitome in common wheat for the first time and lays a foundation for exploring the physiological role of lysine ubiquitination in wheat and other plants.